The port of Singapore authority : competing in a declining Asian economy - Gordon, John (2013)
The case explores how the city state of Singapore developed its natural resources of a large, deep-water harbour and strategic location to become one of the world's leading ports. To overcome physical limitations faced by the port, and to extend port capacity without adding a proportionate number of employees or land, the Port of Singapore Authority (PSA) invested heavily on its Operations Management and Information Technology applications.